Success and Threats in the Clustering of the Automotive Industry in Spain: The Role of Public and Private Agents - Albors-Garrigos, Jose; Collado, Antonio (Management:Journal of Sustainable Business and Management Solutions in Emerging Economies, 2019)
Research Question: This article clarifies the role of clusters in industry agglomeration efficiency as well as the role that public and private agents play in their efficiency. Motivation: The automobile industry in Spain is an exception to the industrial decline suffered by the secondary sector since the economic crisis exploded in Spain. Employment in the vehicle manufacturing industry has recovered significantly in Spain in 2017, with a significant growth bringing it closer to 2008 levels. The sector accounts for 8.6 % of the country’s GNP. How can we explain this success? Are there new threats (technology, environmental standards, emerging economies, etc.) menacing the sector? Based on value chain and cluster theories we explain its success and how new threats could be managed? The response lays in analyzing the role of cluster agents in the various clusters dynamics. The research shows how the openness of clusters plays a crucial role in their sustainability. Idea: Based on value chain and cluster theories we explain their success and how new threats could be managed? The response lays in analyzing the role of cluster agents in the various clusters dynamics. The research shows how the openness of clusters plays a crucial role in their sustainability. Data: primary data was collected in two surveys and interviews campaigns during 2013 and 2017. Furthermore, secondary data from national, regional and sectoral sources were analysed. Tools: The research is based on a series of interviews and visits to the automotive clusters in Spain. Additionally, the authors have analyzed abundant secondary information and web contents available on the clusters agents: manufacturers, suppliers, unions, associations, etc. Findings: The paper concludes that regional and national policies are relevant but that consensus between clusters’ agents is essential for their success. However, will the existing agents be able to withstand new threats? .Contribution: The article contributes to clusters literature and the clusters’ role of the agents in the global value chain context. It also sheds light on public policies to support automotive industries. Limitations are linked to resource limitations.